Evidence that xeroderma pigmentosum cells from complementation group E are deficient in a homolog of yeast photolyase. - Patterson, M (1989)
Xeroderma pigmentosum (XP) patients are deficient in the excision repair of damaged DNA. Recognition of the DNA lesion appears to involve a nuclear factor that is defective in complementation group E (XPE binding factor). We have now identified a factor in the yeast Saccharomyces cerevisiae that shares many properties with XPE binding factor, including cellular location, abundance, magnesium dependence, and relative affinities for multiple forms of damaged DNA. Yeast binding activity is dependent on photolyase, which catalyzes the photoreactivation of pyrimidine dimers. These results suggest that yeast photolyase may also function as an auxiliary protein in excision repair. Furthermore, XPE binding factor appears to be the human homolog of yeast photolyase.